MRI Artifacts and Cochlear Implant Positioning at 3 T In Vivo. Issue 6 (July 2015) - Todt, Ingo; Rademacher, Grit; Mittmann, Philipp; Wagner, Jan; Mutze, Sven; Ernst, Arne
Abstract : Hypothesis: To evaluate the assessment of the internal auditory canal and the labyrinth in relation to different CI magnet positions and MRI sequences at 3 T. Background: The indication criteria for cochlear implantation have been changed over the years and the growing number of implantations in patients after acoustic neuroma resections underline the importance of a postoperative MR imaging to assess the internal auditory canal (IAC) and the labyrinth. The MRI artifact induced by the cochlear implant magnet is a known problem that should be further observed by this investigation. Methods: We compared the artifacts of Cochlear 512 magnets at different head positions in vivo at 3 T. The observed positions varied with a nasion-external ear canal angle of 90, 120, and 160 degrees and a variable distance of 5, 7, and 9 cm in relation to the external ear canal and different MRI sequences. Results: The complete assessment of the internal auditory canal and labyrinth was possible with a magnet positioned at 90 degrees and 9 cm and 160 degrees and 9 cm. Evaluation of the IAC alone was possible with magnet positions at 90 degrees and 7 cm and 9 cm, 120 degrees and 9 cm, and 160 degrees and 7 cm and 9 cm. A high-resolution 3D T2w Drive sequence decreased the visibility of the structures significantly. A high-resolution TSE 2D T2w sequence together with one of the above-described positions allowed sufficient visualization of the structures. Conclusion: The position of the implant and the MRI sequence used determine the assessment of the IAC and the labyrinth at 3 T MRI. A position of the implant magnet at a nasion-external auditory canal angle which is more horizontal and posterior than so far commonly used allows a better visualization of the IAC and the labyrinth at 3 T.